GABAergic synaptic components are largely preserved across human and mouse neuronal models - Rebollo, Beatriz; Abrahamyan, Astghik; Thomale, Ulrich-Wilhelm; Kaindl, Angela M.; Herman, Melissa A.; Rosenmund, Christian (Frontiers in Cellular Neuroscience, 2025)
Synaptic transmission is essential for brain function. But which characteristics of synapse function are so crucial that they are conserved between species? In general, animal models have shaped our understanding of neuronal function, although in recent years our knowledge of human neurophysiology has vastly increased. Comparative analyses between rodent and human neurons have highlighted the similarities and differences in morpho-electrical features, but the extent to which the properties of neurotransmitter release are conserved is underexplored. In this study, we compared the intrinsic properties that determine synaptic strength in cultured GABAergic neurons from mouse and human. Our findings demonstrate that, while passive neuronal properties are different across species, synaptic properties are similar, suggesting that mechanisms of synaptic transmission are conserved between mouse and human neurons. This work provides valuable insight into the extent to which animal models reflect human synaptic components at the single cell level.